Sexual function after loop electrosurgical excision procedure for cervical dysplasia - Inna N. (2014)
Introduction: Loop electrosurgical excision procedure (LEEP) is an effective tool for management of cervical dysplasia. However, removal of a part of the cervix might have a negative impact on sexual function. Aim: To examine the effect of LEEP on overall sexual satisfaction and other specific aspects of sexual function in women with cervical dysplasia. Methods: Eighty-nine premenopausal women with cervical dysplasia who had undergone LEEP at least 3 months previously were interviewed once on post-LEEP follow-up visits with a questionnaire on pre- and post-procedural sexual function. Data on frequency of sexual intercourse, the presence of dysmenorrhea, dyspareunia, and postcoital bleeding were compared using the McNemar test. Data on specific aspects of sexual function rated by the 6-point Likert scale were analyzed using Wilcoxon signed ranks test. Main Outcome Measure: The main outcome is the overall sexual intercourse satisfaction. Results: The mean age was 41.7 years. The median interval from LEEP to the time of interview was 29.3 weeks. The time of resumption of sexual intercourse after LEEP was 8.1 weeks on the average. The changes in the frequency of sexual intercourse, dysmenorrhea, and dyspareunia after LEEP were not statistically significant. The changes in overall satisfaction, vaginal elasticity, and orgasmic satisfaction appeared statistically significant (P < 0.05). Conclusion: Having LEEP done along with other " non-surgical" parts of cervical pre-cancer management is associated with small but statistically significant decreases in overall sexual satisfaction, vaginal elasticity, and orgasmic satisfaction when interviewed near to the procedure at 29.3 weeks post-operation. However, the changes on other aspects of sexual function are insignificant. The LEEP procedure itself appears to have a minimal, if any, clinically important adverse effect on sexual function. © 2009 International Society for Sexual Medicine.